The Social Quarantining of Migrant Labour: Everyday Effects of Temporary Foreign Worker Regulation in Canada - Horgan, Mervyn; Liinamaa, Saara (Journal of Ethnic and Migration Studies, 2017)
Low-wage migrant workers in wealthy nations occupy an ambiguous social and legal status that is inseparable from global economics and politics. This article adds to the growing and diverse literature on temporariness in labour and citizenship by reviewing Canada’s internationally recognised ‘model’ programme, the Seasonal Agricultural Worker Program (SAWP). Specifically, we present research on a small but rapidly growing peripheral pocket of workers in Nova Scotia, a less populated and more economically depressed province. Interview with former SAWP participants demonstrate how the uncertainty characterising the legal, immigration, and employment status of seasonal agricultural workers is socially practised and individually experienced. In particular, we show how specific elements of current migrant labour regulation have everyday effects in organising and delimiting non-work dimensions of migrant workers’ lives. In attending to the spatio-temporal dimensions of migrant workers’ lives we develop the concept social quarantining as a characteristic feature of former workers’ experiences ‘on the contract’.